Computer-Assisted Dental Implant Placement Following Free Flap Reconstruction: Virtual Planning, CAD/CAM Templates, Dynamic Navigation and Augmented Reality - Ochandiano, Santiago; García-Mato, David; Gonzalez-Alvarez, Alba; Moreta-Martinez, Rafael; Tousidonis, Manuel; Navarro-Cuellar, Carlos; Navarro-Cuellar, Ignacio; Salmerón, José Ignacio; Pascau, Javier (Frontiers in Oncology, 2022)
Image guided surgery, virtual planning, 3D printing and CAD/CAM technology is changing head and neck ablative and reconstructive surgical oncology. Due to quality of life improvement dental implant rehabilitation could be considered in every patient treated with curative intent. Accurate implant placement is mandatory for prosthesis long term stability and success in oncologic patients. We present a prospective study, with a novel workflow, comprising 11 patients reconstructed with free flaps and 56 osseointegrated implants placed in bone flaps or remnant jaws (iliac crest, fibula, radial forearm, anterolateral thigh). Starting from CT data and jaw plaster model scannig virtual dental prosthesis was designed. Then prosthetically driven dental implacement was also virtually planned and transferred to the patient by means of intraoperative infrared optical navigation (first four patients) and a combination of static guide conventional teeth supported 3D printed acrylic stent, intraoperative dynamic navigation and augmented reality for final intraoperative verification (last 6 patients). Coronal, apical and angular deviation between virtual surgical planning and final guided intraoperative position were measured on each implant. There is a clear learning curve for surgeons when applying guided methods. Initial only-navigated cases achieved low accuracy but comparable to non guided freehand positioning due to jig registration instability. Subsequent dynamic navigation cases combining highly stable acrylic static guides as reference and registration markers, result in the highest accuracy with a 1-1,5 mm deviation at insertion point. Augmented reality mobile phone navigation APP based, is a valuable tool for intraoperative visualization and final verification although is still a difficult technique for guiding surgery. A fixed screw retained ideal dental prosthesis was achieved in every case as virtually planned. Implant placement, the final step in free flap oncological reconstruction, could be accurately planned and placed with image guided surgery, 3D printing and CAD/CAM technology. The learning curve could be overcome with preclinical laboratory training but virtually designed and 3D printed tracer registration stability is crucial for accurate and predictable results. Applying these concept to our difficult oncologic patients subgroup with deep anatomic alterations ended in comparable results as those reported in non oncologic patients.